PENGARUH KARAKTERISTIK HIS DENGAN LAMA PERSALINAN KALA II DI BPS SAHABAT PEREMPUAN GUNUNG ANYAR SURABAYA - Nisa’, Fauziyatun (Unusa Press, 2016)
Contraction of uterus is the major physiological force during the delivery process of second period. Based on the results of preliminary studies, there is still mother who get pathological second period of childbirth. Intention of this research is to identity influence contraction of uterus characteristics with length of second period. Design this research use analytic with cohort method. The population is all of the mother who have the interpretation of labor on June 14 until July 9 and delivery at private practice midwife Sahabat Perempuan Gunung Anyar Surabaya, which amounts 30 respondents. Big of sample 28 respondents, were teken with probability sampling techniques, that is simple random sampling. Processing by editing, coding and tabulating. Variable independent is contraction of uterus characteristics and variable dependent is length of second period. Result of this research with test of chie-squares with significance level α = 0,05. Most respondents with contraction of uterus characteristics normally is (53,3 % ) only a small proportion who get pathological second period of childbirth (18,75 %). From got by statistical test result of ρ = 0,025 and ρ < α of meaning H1 accepted, it means there is correlation between contraction of uterus characteristics with length of second period at private practice midwife Sahabat Perempuan Gunung Anyar Surabaya. It can see from Odds Ratio (OR) is getting 7,8 (95 % CI : 1,47 – 41,21). Its means contraction of uterus characteristics more effective for length of second period. This research conclusion that there more mother delivering have contraction of uterus characteristics normally, so more big chance mother delivering for felt with length of second period. Adviced to pregnant women to trying the contraction of uterus with pregnancy gymnastic, it can train the muscle strength of the stomach, hips, and other supporting muscle that are not rigid and well coordinated, so the contraction of uterus become normally.